Entransy and its utilization in problems of thermodynamics and heat transfer - Oliveira, Santiago del Rio [UNESP]; Milanez, Luiz Fernando (My University, 2012)
The concept of entransy was recently proposed in terms of the analogy to the electric energy stored in a capacitor. The entransy of a system describes its heat transfer ability, as the exergy of a system quantifies its work production potential. Hence, the concept of entransy can be useful in problems where the heat transfer is the main objective, as for example, in systems collecting solar energy. This concept is quite recent and there are only a few works related to this topic. It is expected, however, that this approach will soon be used more often in the analysis of problems in thermodynamics and heat transfer. The objective of this work is to present a review of the concept of entransy in a systematic way, beginning with its definition, balance equations and a few examples of simple applications. It is hoped that this concept of entransy becomes a useful tool in the analysis and design of more efficient thermal systems. © 2012 Praise Worthy Prize S.r.l.- All rights reserved.
Keywords: Entransy; Entropy; Exergy; Heat transfer; Thermodynamics